Analysis Of Student Perceptions Of The Use Of Artificial Intelligence In Science Learning In Elementary School - Wirawan, Zose; Arwien, Rizki Trisnawaty; Muriati, St. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
The aim of this research is to analyze students' perceptions regarding the application of artificial intelligence in science learning materials. The research method used in this study is a descriptive quantitative approach to evaluate the perceptions of elementary school students towards the implementation of artificial intelligence (AI) in science education in Makassar in June 2024. Data analysis techniques involve descriptive statistics. The subjects of the study consisted of 26 students, with instrument being a 24-item questionnaire using a Likert scale from 1 to 5. This questionnaire was designed to assess students' learning experiences, interests, motivation, benefits, impacts, as well as challenges and expectations. The results indicate that the use of AI in science learning has a significant positive impact, enhancing students' learning experiences, interests, and motivation. The majority of students reported that AI aided them in understanding the material, exam preparation, and learning outcomes. However, there were some challenges such as technical issues and adaptation that need to be addressed. Students have high expectations for the sustainability of this technology. To optimize the benefits of AI and overcome challenges, technical support, training, and adequate infrastructure are needed so that all students can equitably benefit from this technology.